Training Manual: Gender Integration for Smallholder Livestock Keepers (Amharic Version) - Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2022)
This manual engages smallholder farmers on women’s participation at every level of the livestock value chain, where they face influences from factors, including their skills, their access to capital; capacities, organizational skills, and their limitations. Women face higher transaction costs in marketing and are less likely than men to be served by formal financial institutions. As livestock production becomes increasingly market-oriented, women may no longer be able to compete with men or gain the same benefits. Therefore, it is imperative that gender integration in livestock development considers how to enhance the position of women and influence strategic gender relations.